PENDEKATAN PARADIGMA PEDAGOGIK REFLEKTIF DALAM PEMBELAJARAN SEJARAH UNTUK MENINGKATKAN KOMPETENSI 4C DI ABAD 21 - Debi Setiawati; Fatmawati Fatmawati (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
Learning challenges in the era of globalization are expected to produce human resources who have complete competence to face world competition. For this reason, 21st century competency skills are needed for students including critical thinking and problem solving skills, Communication Skills, Creativity And Innovation Skills, and Collaboration Skills (4C). The role of the teacher in learning history is very decisive in the formation of 21st century skills. Teachers must be able to develop learning media, learning models and learning methods that are innovative and contextual, so as to foster historical awareness. This article aims to describe and inform the reflective pedagogic paradigm approach that can be used as a model of history learning approach in fulfilling 21st century competency skills. Learning in the era of globalization is oriented towards data collection, data analysis, problem solving and collaboration. The reflective pedagogic paradigm can be used as an approach to learning history that can develop students to become fully human beings both in Competence conscience and Compassion (compassion for others) so that they can respond to educational challenges in the era of globalization.